2017
DOI: 10.3389/fnins.2017.00182
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Intake Augments Excitability of PVN Neurons in Rats: Role of the Endoplasmic Reticulum Ca2+ Store

Abstract: High salt (HS) intake sensitizes central autonomic circuitry leading to sympathoexcitation. However, its underlying mechanisms are not fully understood. We hypothesized that inhibition of PVN endoplasmic reticulum (ER) Ca2+ store function would augment PVN neuronal excitability and sympathetic nerve activity (SNA). We further hypothesized that a 2% (NaCl) HS diet for 5 weeks would reduce ER Ca2+ store function and increase excitability of PVN neurons with axon projections to the rostral ventrolateral medulla (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…Graded current injections evoked graded increases in firing frequency and reached saturation at +200 pA current in NS neurons. This data confirms our previous findings regarding PVN-RVLM neuronal excitability between NS and HS-treated rats [ 24 ]. Apamin, a potent SK channel blocker, significantly increased neuronal firing frequency in NS neurons compared to NS neurons without apamin (+200 pA, 49.4 ± 3.2 versus 18.5 ± 2.5 Hz, P < 0.05).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Graded current injections evoked graded increases in firing frequency and reached saturation at +200 pA current in NS neurons. This data confirms our previous findings regarding PVN-RVLM neuronal excitability between NS and HS-treated rats [ 24 ]. Apamin, a potent SK channel blocker, significantly increased neuronal firing frequency in NS neurons compared to NS neurons without apamin (+200 pA, 49.4 ± 3.2 versus 18.5 ± 2.5 Hz, P < 0.05).…”
Section: Resultssupporting
confidence: 93%
“…It has been demonstrated that the SK channels also play an important role in controlling the in vitro excitability of presympathetic PVN-RVLM neurons and in vivo sympathetic outflow in rats [ 3 , 23 ]. Moreover, we have reported that downregulation of SK channel function among the PVN neurons contributed to the sympathoexcitation in rats with chronic HS intake (5 weeks of 2% NaCl) [ 24 ]. Furthermore, our recent study indicates that depletion of endoplasmic reticulum (ER) Ca 2+ store likely plays a role in increasing PVN-RVLM neuronal excitability, which may underlie the mechanisms of sympathoexcitation in rats with HS intake [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in action potential in excitable tissues is the result of a large and rapid Na + influx [32]. It has been reported that high salt intake increases the excitability of some neurons in rodents [33,34]. We therefore assumed that HSD might disrupt morning anticipation behavior by increasing excitability in PDF neurons, and the GAL4-UAS system is the appropriate tool to test this assumption [35].…”
Section: Enhancement Of Excitability In Pdf Neurons Mimics the Hsd That Causes Morning Anticipation Impairmentmentioning
confidence: 99%
“…While we cannot rule out acetate induced modulation of other voltage-gated K + channels or small conductance calcium activated K + channels (SK-channels), SK-channel involvement is highly unlikely as SK-channel loss of function has been demonstrated to increase neuronal excitability. 44,65,66…”
Section: Possible Involvement Of Large-conductance Ca 2+ and Voltage-gated K + Channels (Bkchannels) In Acetate Responsementioning
confidence: 99%